DEVELOPING A MARKETING STRATEGY USING SWOT ANALYSIS IN THE DIGITAL ERA ON MOOI DONUT MSMES ON KALIMANTAN STREET, SUMBERSARI DISTRICT, JEMBER REGENCY - Fitria, Aulia ul; Izzuddin, Ahmad; Tyas, Wenny Murtalining (Dynamic Management Journal, 2024)
Study aims to analyse the strategies to enchance the sales of Donat Mooi, a micro, small, and medium enterprise (MSME), in the digital era where consumers are increasingly adopting online purchasing. The study proposes using SWOT analysis as a strategy to address competition and improve the business's competitiveness. The focus is on identifying effective marketing alternatives to overcome challenges faced by Donat Mooi. The qualitative-descriptive method use with direct interviews, observations also literature reviews. It shows from SWOT analysis and Internal-External Matrix indicate the Donat Mooi currently holds a "Hold and Maintain" position. This analysis identifies the potentials and challenges encountered by the enterprise in the digital market. The recommended strategy emerging from this research is an intensive-aggressive approach, enabling Donat Mooi to leverage its internal strengths while addressing threats and capitalizing on external opportunities more effectively. Thus, this study not only provides insights into the current conditions of Donat Mooi but also offers concrete guidelines for actions aimed at enhancing competitiveness and ensuring the sustainability of the business in an evolving digital landscape.